ANALISIS RENCANA PELAKSANAAN PEMBELAJARAN DARING GURU KELAS IV SEKOLAH DASAR NEGERI 34 PONTIANAK KOTA - Frensy Graselie Lantu; Kartono Kartono; Rio Pranata (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to describe the preparation of an online learning implementation plan by grade IV teachers at the 34 Pontianak City Elementary School during the Covid19 Pandemic. The research method used is descriptive in the form of qualitative research. The source of the data for this research is the fourth-grade teacher of the 34 Pontianak City Elementary School and the data is the online Learning Implementation Plan (RPP) document and the results of interviews with the fourthgrade teacher of the 34 Pontianak City Elementary School. The results of the analysis show that the components of the learning implementation plan prepared by the teacher have been guided by the SE Kemendikbud Number 14 of 2019 regarding the simplification of the Learning Implementation Plan, but on the completeness and regularity of the component preparation there are criteria that are not appropriate for the components of objectives, learning scenarios and learning evaluation. Components that meet the appropriate criteria are learning media and learning resources. The implementation of TPACK, HOTS and STEAM elements of innovative 21st century learning is not described in writing in the learning step.Keywords: Analysis, Learning Implementation Plan, Online